Patients' perspectives of the skills and competencies of therapy radiographers/radiation therapists (TRs/RTTs) in the UK, Portugal and Malta; a qualitative study from the SAFE Europe project. (May 2023) - Flood, T.; O Neill, A.; Oliveira, C.M.; Barbosa, B.; Soares, A.L.; Muscat, K.; Guille, S.; McClure, P.; Hughes, C.; McFadden, S.
Abstract: Introduction: The role of the Therapy Radiographer/Radiation Therapist (TR/RTT) is to provide radiotherapy to patients with a cancer diagnosis. This includes, not only administration of treatment, but also management of side-effects and provision of support/care. Despite this role being consistent throughout Europe, there is currently no standardisation of education for TRs/RTTs. The SAFE EUROPE project aims to standardize TR/RTT education to enable 'safe and free exchange' of TRs/RTTs across Europe. Consequently, this study aims to explore patients' perspectives regarding the current skills and competencies of TRs/RTTs. Methods: From May 2021 to February 2022, semi-structured interviews were conducted with patients who had recently received radiotherapy in the UK, Malta and Portugal. Ethical approval for this study was granted by the NHS Research Ethics Committee with additional local approvals obtained. Results: Forty-eight participants from the UK (n = 18), Portugal (n = 19), and Malta (n = 11) completed interviews. Participants described high satisfaction with TRs'/RTTs' competence and skills in all three countries. The main theme arising from the analysis was the importance of trust building with TRs/RTTs. Six factors were identified as influencing levels of trust: communication; side-effect management; team consistency; relational skills; patient dignity; and competence. A small number of patients reported feeling rushed and not having their physical and emotional needs met by TRs/RTTs. Conclusion: This multicentre study demonstrated that patients perceive TRs/RTTs in the UK, Malta and Portugal as highly competent and skilled. Practical recommendations are provided to address identified deficits in practice, which can be addressed through adaptation of TR/RTT education/training and clinical practice. Implications for practice: Recommendations arising from this study are important to ensure that TRs/RTTs have transferable skills that provide consistently high quality care to patients throughout Europe.